Host plant-derived benzoic acid interferes with 4-hydroxybenzoic acid degradation in the phytopathogen Xanthomonas campestris by competitively binding to PobR - Bo Chen; Lian Zhou; Kai Song; Chitti Thawai; Ya-Wen He (Phytopathology Research, 2024)
Abstract Xanthomonas campestris pv. campestris (Xcc) is the causal agent of black rot in Brassica vegetables, which can induce the host plant to produce salicylic acid and 4-hydroxybenzoic acid (4-HBA) during infection. Xcc was previously shown to sense and degrade host plant-derived 4-HBA via the sensor PobR and a PobA-dependent pathway. The degradation of 4-HBA is associated with Xcc virulence in cabbage. The present study generated a reporter strain XC1::PpobA-gusA to monitor pobA transcription. 4-HBA-like compounds were screened for their ability to interfere with pobA transcription. Benzoic acid (BA) was found to efficiently decrease pobA transcription in a dose-dependent manner. Xcc neither produced nor degraded BA; however, the exogenous addition of BA to the 4-HBA-containing Xcc culture significantly decreased the 4-HBA degradation rate. Furthermore, addition of BA into the Xcc culture did not significantly affect the transcription of pobA or pobR; however, addition of BA into the 4-HBA-containing culture significantly decreased the transcription of both genes. Isothermal titration calorimetry and an electrophoretic mobility shift assay revealed that BA binds to PobR with a moderate affinity, which interfered with the binding of 4-HBA/PobR complex to the pobA promoter and thereby inhibiting pobA transcription and 4-HBA degradation. The endogenous BA level of the infected cabbage leaves increased in response to Xcc infection. In the presence of BA, the virulence of Xcc on cabbage decreased significantly. Taken together, these results suggest that cabbage utilizes BA to interfere with 4-HBA degradation, thereby reducing Xcc virulence. Thus, BA has the potential to be developed as a bactericide against Xcc infection.